Fructose-1,6-bisphosphatase Inhibitors. 2. Design, Synthesis, and Structure−Activity Relationship of a Series of Phosphonic Acid Containing Benzimidazoles that Function as 5′-Adenosinemonophosphate (AMP) Mimics - Dang, Qun; Kasibhatla, Srinivas Rao; Xiao, Wei; Liu, Yan; DaRe, Jay; Taplin, Frank; Reddy, K. Raja; Scarlato, Gerard R; Gibson, Tony; van Poelje, Paul D; Potter, Scott C; Erion, Mark D (Journal of medicinal chemistry, 2010)
Efforts to enhance the inhibitory potency of the initial purine series of fructose-1,6-bisphosphatase (FBPase) inhibitors led to the discovery of a series of benzimidazole analogues with human FBPase IC50s < 100 nM. Inhibitor 4.4 emerged as a lead compound based on its potent inhibition of human liver FBPase (IC50 = 55 nM) and significant glucose lowering in normal fasted rats. Intravenous administration of 4.4 to Zucker diabetic fatty rats led to rapid and robust glucose lowering, thereby providing the first evidence that FBPase inhibitors could improve glycemia in animal models of type 2 diabetes.